Simulation of commutation process DC traction motor of quarry dump truck - V. V. Kharlamov; Yu. V. Moskalev; S. N. Naiden (Омский научный вестник)
The article considers a nonlinear multiple regression model based on which a model of the commutation process of the DC traction motor of a quarry dump truck. The regression model is constructed using experimental data of the traction engine operation obtained from an automated video measurement system for evaluating commutation in operation. The proposed mathematical model establishes a relationship between the values of the armature voltage, armature current, excitation current, and the spark intensity of the collector-brush node. The adequacy of the mathematical model is confirmed by comparing the degree of sparking obtained experimentally and using the proposed model. The relative error value of the experimental and calculated data for different values of the armature voltage, armature current, and excitation current from the model adequacy range does not exceed the allowed values.